Strengthening the dissemination of the law in order to protect the rights and interests of members and employees in the current period - THANH XUÂN, HOÀNG (Tạp chí Nghiên cứu Khoa học Công đoàn, 2019)
Propaganda education is one of the three basic functions of the Vietnam Trade Union. Therefore, in order to protectlegitimate legitimate interests of union members and workers in the current period, the Trade Union organization should constantlyenhance the propaganda and education of employers and workers. This is to raise the awareness of the line leader of the Party ofState's legal policies, including the legal knowledge of labor and trade unions.